Diffraction Imaging in Hard-rock Environments - Bóna, Andrej; Pevzner, Roman; Tertyshnikov, Konstantin; Greenwood, Andrew; Sun, Bai Chun; Yavuz, S.; Urosevic, Milovan (EAGE, 2013)
Herein, we expand and use the method used by Landa and Keydar (1998) to detect local heterogeneities. The method relies on computing local semblance along the diffraction offset-traveltime curves. We expand the method by taking into account the phase change occurring for edge diffractions. We demonstrate the usefulness of the method on hard-rock seismic data.